2006
DOI: 10.1213/01.ane.0000181321.55422.c6
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Recovery After General Anesthesia Combined with Neuromuscular Blocking Drugs

Abstract: Previous studies suggest that women recover faster from general anesthesia than men, but it is unclear whether this is a result of a gender effect or differences in the pattern of drug administration or type of surgery. We performed a subset analysis comparing recovery characteristics from general anesthesia combined with neuromuscular blocking drugs of female and male patients, at risk of awareness, enrolled in a large trial testing the effectiveness of bispectral index (BIS) monitoring. We used multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Buchanan et al [28] proposed that gender has an independent effect on recovery times in patients undergoing general anesthesia. They concluded that women are less sensitive to the hypnotic effect of anaesthetic drugs than men and may help explain faster recovery times in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchanan et al [28] proposed that gender has an independent effect on recovery times in patients undergoing general anesthesia. They concluded that women are less sensitive to the hypnotic effect of anaesthetic drugs than men and may help explain faster recovery times in women.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the combination of TIVA and continuous epidural anesthesia would be useful to maintain stable hemodynamic state and to obtain early recovery time, especially in the elderly. [23][24][25]28,30,41] The combination of TIVA and epidural anesthesia does not require the use of intraoperative intravenous opioids and shortens recovery time without increasing the incidence of side effects [41][42][43] and reduce the dose consumption of IV and inhalation anaesthetics. [44][45][46] We used 0.1% bupivacaine combined with 2µg/ mL fentanyl infusion doses in our study, and found that MAP values on 10 th min.…”
Section: October 2015 177mentioning
confidence: 99%
“…6 In a study of 1079 patients, Buchanan et al demonstrated similar findings and proposed that lower sensitivity to the hypnotic effect of anesthetics in women may account for their faster recovery. 7 The female sex hormone that affected pharmacokinetics and pharmacodynamics of anesthetics was postulated to play a role in the gender differences in recovery time. 19 Further investigations are needed to elucidate the relationship between sex hormone and recovery from anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Data about improving the recovery process by BIS-titrated anesthetic agents have been inconsistent. The recovery process appears to be dependant on factors such as age, gender, ASA physical status, and duration of anesthesia (6,7). The objective of this study was to assess the effects of BIS-guided general anesthesia in combination with thoracic epidural analgesia on recovery times and early mobilization in patients undergoing elective fast-track colon surgery.…”
mentioning
confidence: 99%